# Square of Triangular Number equals Sum of Sequence of Cubes/Proof 2

## Theorem

$\displaystyle \sum_{i \mathop = 1}^n i^3 = {T_n}^2$

where $T_n$ denotes the $n$th triangular number.

## Proof

The proof proceeds by induction.

For all $n \in \Z_{> 0}$, let $\map P n$ be the proposition:

$\displaystyle \sum_{i \mathop = 1}^n i^3 = {T_n}^2$

### Basis for the Induction

$\map P 1$ is the case:

 $\displaystyle \sum_{i \mathop = 1}^1 i^3$ $=$ $\displaystyle 1^3$ $\displaystyle$ $=$ $\displaystyle 1$ $\displaystyle$ $=$ $\displaystyle \paren {\frac {1 \paren {1 + 1} } 2}^2$ $\displaystyle$ $=$ $\displaystyle {T_1}^2$ Closed Form for Triangular Numbers

Thus $\map P 1$ is seen to hold.

This is the basis for the induction.

### Induction Hypothesis

Now it needs to be shown that, if $\map P k$ is true, where $k \ge 2$, then it logically follows that $\map P {k + 1}$ is true.

So this is the induction hypothesis:

$\displaystyle \sum_{i \mathop = 1}^k i^3 = {T_k}^2$

from which it is to be shown that:

$\displaystyle \sum_{i \mathop = 1}^{k + 1} i^3 = {T_{k + 1} }^2$

### Induction Step

This is the induction step:

 $\displaystyle \sum_{i \mathop = 1}^{k + 1} i^3$ $=$ $\displaystyle \sum_{i \mathop = 1}^k i^3 + \paren {k + 1}^3$ $\displaystyle$ $=$ $\displaystyle {T_k}^2 + \paren {k + 1}^3$ Induction Hypothesis $\displaystyle$ $=$ $\displaystyle {T_k}^2 + \paren { {T_{k + 1} }^2 - {T_k}^2}$ Cube Number as Difference between Squares of Triangular Numbers $\displaystyle$ $=$ $\displaystyle {T_{k + 1} }^2$

So $\map P k \implies \map P {k + 1}$ and the result follows by the Principle of Mathematical Induction.

Therefore:

$\forall n \in \Z_{> 0}: \displaystyle \sum_{i \mathop = 1}^n i^3 = {T_n}^2$

$\blacksquare$